2006
DOI: 10.1111/j.1365-2583.2006.00662.x
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide analysis of phenobarbital‐inducible genes in Drosophila melanogaster

Abstract: An oligoarray analysis was conducted to determine the differential expression of genes due to phenobarbital exposure in Drosophila melanogaster (w(1118) strain) third instar larvae. Seventeen genes were observed to be induced with increased expression by a statistical analysis of microarrays approach with a q < or = 0.05. At q < or = 0.12, four more genes (Cyp12d1, DmGstd4, and two genes with unknown function) were found to be up-regulated, and 11 genes with unknown function were found to be down-regulated. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 95 publications
3
52
0
3
Order By: Relevance
“…Other microarray experiments performed by challenging D. melanogaster to a wide variety of conditions, such as exposure phenobarbital (40)(41)(42)76), ethanol (77,78), starvation (79), and looking at transcriptome changes in response to aging (80) identified a number of P450s that alter expression levels in response to variations in these parameters. We highlight 2 examples in which tissue-expression data can be used to extend microarray results.…”
Section: Temporal Expression Differences Of P450 Between Embryos Andmentioning
confidence: 99%
“…Other microarray experiments performed by challenging D. melanogaster to a wide variety of conditions, such as exposure phenobarbital (40)(41)(42)76), ethanol (77,78), starvation (79), and looking at transcriptome changes in response to aging (80) identified a number of P450s that alter expression levels in response to variations in these parameters. We highlight 2 examples in which tissue-expression data can be used to extend microarray results.…”
Section: Temporal Expression Differences Of P450 Between Embryos Andmentioning
confidence: 99%
“…PB induction of P450s has been demonstrated in Drosophila melanogaster (Sun et al, 2006), Helicoverpa zea , Blatella germanica (Brown et al, 2003), and Aedes aegypti (Sousa-Polezzi and Bicudo, 2004). Caffeine has also been reported to induce P450s in D. melanogaster (Bhaskara et al, 2006;Willoughby et al, 2006).…”
Section: Introductionmentioning
confidence: 91%
“…It has been well documented that some P450s could be induced by PB, which is one of the most commonly used inducers of P450s. According to a genome-wide analysis of PB-inducible genes in D. melanogaster, some P450 genes (e.g., CYP6A2) associated with metabolic pesticide resistance were observed to be PB-induced with increased expression (Sun et al, 2006). Londoño et al (2004) reported that atrazine induces a family 4 cytochrome P450 gene in Chironomus tentans (Diptera: Chironomidae).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A common evolutionary ancestor in terms of gene family is also possible, especially given only 41% identity (Table 3.3). CYP4AY1 also shared identity with a Tribolium castaneum P450 similar to CYP4D14, which in third instar larvae of Drosophila melanogaster exhibited increased expression with pheonbarbital exposure (Sun et al, 2006). Pheonbarbital exposure induces some of the same genes as pesticide exposure does in resistant strains, so is applied to find genes related to pesticide resistance.…”
Section: Possible Functions Of Cyp4ay1mentioning
confidence: 99%